Avoiding broadband radiation damping effects in NOESY spectra - Kelsey Anne Marr; Alexej Jerschow (Journal of Magnetic Resonance Open)
Radiation damping is a well-known phenomenon in the context of NMR spectroscopy. Several strategies exist for minimizing the effects of radiation damping, which have mostly been focused on limiting the effects of one resonance (frequently the water resonance). When samples with many resonances are examined at high concentration, such approaches often cannot be used. One category of systems where the broadband nature of radiation damping leads to complications are deep eutectic solvents (DESs). DESs are considered innovative solvent systems that have several advantages such as tunability and environmental friendliness, with important applications ranging from catalysis to drug delivery. It is of interest to examine the intermolecular effects via NMR spectroscopy in these systems. Here we show that broadband radiation effects are very strong in these systems and identify simple strategies specifically for 2D NOESY NMR spectroscopy to regain the ability to quantify intermolecular interactions in these systems.